Association of term isolated microcephaly with mode of delivery and perinatal outcome - a retrospective case-control analysis - Ron Bardin; Eyal Krispin; Lina Salman; Inbal Navon; Anat Shmueli; Sharon Perlman; Yinon Gilboa; Eran Hadar (BMC, 2021)
Abstract Background We aimed to evaluate the association of isolated fetal microcephaly measured by ultrasound prior to delivery at term with mode of delivery and perinatal outcome. Methods A single-center retrospective study was conducted in 2012-2016. Fetal microcephaly was defined as head circumference > 2 standard deviations of the mean for gestational age and sex. We compared the obstetric, delivery, and outcome parameters of women in whom ultrasound performed up to 10 days prior to term delivery showed isolated fetal microcephaly (study group) or normal head circumference (reference group). Exclusion criteria were intrauterine fetal death, birthweight below the 10th percentile, and antepartum cesarean delivery for any indication. Results Of 3677 women included in the study, 26 (0.7%) had a late ultrasound finding of isolated fetal microcephaly. Baseline characteristics were similar in the two groups except for estimated fetal weight based on abdominal circumference and biparietal diameter, which was lower in the microcephaly group (3209.8 ± 557.6 vs. 2685.8 ± 420.8 g, p < .001). There was no significant between-group difference in rate of vaginal operative deliveries (11.7% vs 14.8%, respectively, p = 0.372). The study group had no intrapartum cesarean deliveries compared to 6.3% of the reference group (NS). Compared to controls, neonates in the study group were smaller (3323.2 ± 432.2 vs. 2957.0 ± 330.4 g, p < .001), with lower birthweight percentile (60.5 ± 26.5 vs. 33.6 ± 21.5%, p < .001) and were more often males (48.2 vs. 90.0%, p < .001). No significant differences were noted in perinatal outcomes between the groups, including admission to neonatal intensive care unit, intraventricular hemorrhage, 5-min Apgar score < 7, asphyxia, seizures, and sepsis. Conclusions Isolated microcephaly in term fetuses is not advantageous for a vaginal delivery, nor does it does not pose a greater than normal risk of adverse perinatal outcome.